SAT0425 Management of Carpal Tunnel Syndrome in Musculoskeletal Disease Department: Are we Adhering to the Guideline?. (23rd January 2014) - Md Yusof, M. Y.; Chattopadhyay, C.; Gladston Chelliah, E.; Sathi, N.
Abstract : Background: Carpal tunnel syndrome (CTS) is a common nerve entrapment neuropathy caused by compression of median nerve as it travels through the anatomic carpal tunnel. It is a clinical diagnosis, hence identifying the risk factors for CTS and assessment of clinical severity is vital in guiding the management. Despite a common disease, the management of CTS varies among the clinicians as it lacks a unified National Guideline. The only Guideline that is available is from the British Society of Surgery of the Hands (BSSH). Objectives: The aim of our the study is to compare the practice of both the rheumatologist and the orthopaedics surgeon in terms of compliance to the BSSH management of carpal tunnel syndrome guideline. Methods: 50 patients consisted of 25 from each specialty (Rheumatology & Orthopaedics) who received treatment from our Musculoskeletal Disease department were identified retrospectively from January 2011 to July 2012. This was done using the code for CTS, carpal tunnel injection & carpal tunnel decompression. The data is collected from the electronic patient record and subsequently verified with the case notes. We audited the practice in terms of the record of provocative manoeuvres such as Phalen's test, identifying the risk factors & causes for CTS, basic investigations such as glucose and thyroid function tests, assessment of clinical severity and treatment employed such as wrist splints, steroid injection or surgical decompression based on clinical severity. Results: There were 18 male and 32 female patients. Both groups were nearly matched in terms of gender distribution, mean age and mean duration of symptoms. The patients in the Orthopaedics group had a more severe symptom. Provocative manoeuvres were only recorded in only 1/2 of the cases by the Rheumatologist. Risk factors for CTS only identified in about 2/3 of the cases in both groups. Basic important investigations were not requested by Orthopaedics. The assessment of clinical severity was satisfactorily undertaken by the Orthopaedics and Rheumatologist, 92% & 80% respectively. Night splint was only provided in 12% of the patient by the Orthopaedics. Treatment strategies were adhered in majority of cases; Orthopaedics mainly surgical as majority had a moderate to severe disease, Rheumatologist mainly medical as majority had a mild to moderate disease. Conclusions: The current practice of both the Rheumatologists and the Orthopaedic surgeons are not in full compliance to the existing BSSH Guideline of management of CTS. This is largely due to that clinicians are not familiar with such guideline. We are working on a Regional Guideline that can be used as a shared care between the primary and secondary care. Other recommendations include a checklist proforma of CTS management protocol to be placed in the out-patient trolley for use and also the use of Global Symptom Score (GSS) in order to assess response quantitatively to both pre and post-treatment of CTS. Disclosure of Interest: None Declared